Examining the association between rurality and positive childhood experiences among a national sample. Issue 1 (27th August 2022) - Crouch, Elizabeth; Probst, Janice C.; Shi, Sylvia; McLain, Alexander; Eberth, Jan M.; Brown, Monique J.; Merrell, Melinda; Bennett, Kevin J.
Abstract: Purpose: The present study examines the association between rurality and positive childhood experiences (PCEs) among children and adolescents across all 50 states and the District of Columbia. Recent work has quantified the prevalence of PCEs at the national level, but these studies have been based on public use data files, which lack rurality information for 19 states. Methods: Data for this cross‐sectional analysis were drawn from 2016 to 2018 National Survey of Children's Health (NSCH), using the full data set with restricted geographic data (n = 63, 000). Descriptive statistics and bivariate analyses were used to calculate proportions and unadjusted associations. Multivariable regression models were used to examine the association between residence and the PCEs that were significant in the bivariate analyses. Findings: Rural children were more likely than urban children to be reported as having PCEs: volunteering in their community (aOR 1.29; 95% CI 1.18‐1.42), having a guiding mentor (aOR 1.75; 95% CI 1.45‐2.10), residing in a safe neighborhood (aOR 1.97; 95% CI 1.54‐2.53), and residing in a supportive neighborhood (aOR 1.10; 95% CI 1.01‐1.20) than urban children. Conclusions: The assessment of rural‐urban differences in PCEs using the full NSCH is a unique opportunity to quantify exposure to PCEs. Given the higher baseline rate of PCEs in rural than urban children, programs to increase opportunities for PCEs in urban communities are warranted. Future research should delve further into whether these PCEs translate to better mental health outcomes in rural children.